1998
DOI: 10.1109/16.658840
|View full text |Cite
|
Sign up to set email alerts
|

An efficient approach to noise analysis through multidimensional physics-based models

Abstract: The paper presents a general approach to numerically simulate the noise behavior of bipolar solid-state electron devices through a physics-based multidimensional device model. The proposed technique accounts for noise sources due to carrier velocity and population fluctuations. The power and correlation spectra of the external current or voltage fluctuations are evaluated through a Green's function, linear perturbation theory equivalent to the classical Impedance Field Method for noise analysis and its general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 13 publications
1
78
0
1
Order By: Relevance
“…This model applies when the correlation time of a noise process is much shorter than the period of an applied largesignal bias and is applicable to microscopic diffusion noise and GR noise phenomena. Consider a noise process given by (10) where is the modulating function described by (11) and is an instantaneous function of the solution variables and is a unit stationary noise source with (12) where is a random phase angle and . It can be shown that the CSD between noise phasors at sideband frequencies and is then [3] (13)…”
Section: ) Modulated Stationary Noise Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This model applies when the correlation time of a noise process is much shorter than the period of an applied largesignal bias and is applicable to microscopic diffusion noise and GR noise phenomena. Consider a noise process given by (10) where is the modulating function described by (11) and is an instantaneous function of the solution variables and is a unit stationary noise source with (12) where is a random phase angle and . It can be shown that the CSD between noise phasors at sideband frequencies and is then [3] (13)…”
Section: ) Modulated Stationary Noise Modelmentioning
confidence: 99%
“…This method was typically used to get analytic results for both velocity fluctuation and generation-recombination (GR) transition-rate fluctuations [9]. The IFM was extended to partial differential equation (PDE)-based semiconductor device simulation [10]. These techniques were then extrapolated for the case of device simulation of cyclostationary noise under periodic steady-state conditions [1], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The physics-based noise models are implemented into the device simulator using the impedance field method (IFM) [2]. Two elements are required to calculate the noise at the contact terminals.…”
Section: Methodsmentioning
confidence: 99%
“…FLOODS is capable of doing two-dimensional dc, ac, and transient simulations. Recently, diusion and 1/f Hooge noise models were implemented in FLOODS by Bosman et al [1,2] and by Bonani et al [3] in a similar simulator. The latter noise models based on velocity and mobilitȳ uctuations, respectively, are implemented by adding Langevin noise sources to the electron and hole continuity equations.…”
Section: Introductionmentioning
confidence: 99%
“…The total voltage noise spectral density observed at the contact terminals follows from integration over all noise sources. The g±r noise sources representing transition rate¯uctuations can eectively be accounted for by adding Langevin noise sources to PoissonÕs equation [3] as will be shown below. By utilizing the GreenÕs function already calculated by FLOODS, the g±r noise spectral voltage density contact contribution from each local g±r noise source can be calculated.…”
Section: Introductionmentioning
confidence: 99%